PERHITUNGAN MODEL DWBA DENGAN KOD DWUCK-4: TAMPANG LINTANG HAMBURAN NEUTRON ELASTIK DAN INELASTIK PADA REAKSI 94ZR(N,N) - Syafarudin (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
The calculation of cross section for neutron and 94Zr nuclide collision has been done using the DWBA model and DWUCK-4 code. The optical model potential (OMP) parameters used for the calculation were based on the Becchetti-Greenlees, Rapaport as well as Walter-Guss versions. A Spectrum of total cross section has been resulted with incoming energy range of 1-35 MeV, and a spectrum of energy distribution of cross section has been resulted at the incoming energy of 15 MeV. The calculation result shows that the three OMPs give similar recommendations on cross section for the elastic reaction (n,n) curve, as well as inelastic reaction (n,n’). It is understood from the calculated energy distribution of cross section, that all those OMPs indicate the maximum cross section for the 94Zr(n,n) reaction, En = 15 MeV at almostly the same outgoing energy level, i.e. 7-8 MeV.